Investigating learner autonomy-supportive features in an EFL textbook and perceptions of teachers and students on the textbook role in fostering learner autonomy - Nurul Anggraini; Gin Gin Gustine; Sitti Nurfaidah; La Ode Musaldin (Journal on English as a Foreign Language, 2025)
Textbooks play a crucial role in EFL learning as a bridge between curriculum objectives and classroom practices. However, a growing body of research indicates that many EFL textbooks remain insufficient in facilitating the learning process, particularly in fostering learner autonomy (LA). This qualitative case study aimed to investigate what LA-supportive features are represented in the instructional content of the textbook When English Rings A Bell (WERAB) and explored teachers' and students’ perspectives on the textbook role in promoting LA. The study involved two English teachers and two Grade VII students from a public junior high school in Indonesia. Data were collected through document analysis and semi-structured interviews, and analyzed using content analysis and cyclical coding. The results indicate that textbook WERAB instructions predominantly aligned with lower levels of LA, namely awareness and involvement, while rarely fostering higher-order autonomy such as creation or transcendence. Moreover, teachers and students perceived the textbook instructions as monotonous, lacking scaffolding, overly directive, and offering limited multimodal texts. Students’ language barriers also led teachers to overuse L1, reinforcing their reliance on translation. This study underscores the need for improved instructional design that incorporates autonomy-supportive principles and stronger pedagogical frameworks for more effective future classroom practices.